Editorial, vol. 17, no. 44 - Pera, Bożena; Pasierbek, Wit (Horyzonty Wychowania, 2019)
In the face of dynamic changes brought about by the processes of globalisation and regionalism, and the accompanying scientific and technological progress, growing competition, widely used information and communication technologies, as well as the increasing internationalisation of firms, the approach to entrepreneurship, which affects not only the development of organisations, but also of sectors, countries, regions and even the world economy, is also changing. The problem is also the complexity of processes and connections between economic entities, institutions and societies functioning in different spatial dimensions. The knowledge as well as understanding of all these problems are a challenge for modern economic and entrepreneurial education, conducted at all levels of education.